Pengembangan Media Interaktif Renderforest untuk Meningkatkan Hasil Belajar Teks Negosiasi Siswa Kelas X SMK Musda Perbaungan - Susanti, Elvira; Safina, Nila; Kartika, Rika (Sintaks: Jurnal Bahasa & Sastra Indonesia, 2024)
This research aimed to evaluate the effectiveness and feasibility of Render Forest interactive media on negotiation text material for class X at Vocational School Musda Perbaungan. The study involved 32 students as samples and utilized assessments from material and design expert validators. The results showed that the development was categorized as "Feasible." Material expert I rated it 84% ("Decent"), and material expert II rated it 81.33% ("Decent"). Media expert I rated it 94% ("Very Appropriate"), and media expert II rated it 80% ("Decent"). The Indonesian language teacher's assessment was 89.09% ("Very Decent"). The findings suggest that using Render Forest-assisted teaching materials significantly enhances the learning process. Overall, the study concludes that the interactive media is highly effective and suitable for classroom use, providing a valuable resource for improving student engagement and understanding of negotiation texts.